A numerical approach for evaluating residual capacity of fire damaged concrete members - Kodur, Venkatesh; Agarawal, Ankit (Revista ALCONPAT, 2020)
This paper presents an approach to evaluate residual capacity of fire-damaged concrete structures. The approach involves capturing response in three stages; namely, structural response at ambient conditions (prior to fire exposure), thermo-mechanical response during fire exposure, and post-fire residual response after cooling down of the structural member. The proposed approach is implemented in a comprehensive numerical model developed in the finite element computer program ABAQUS for specifically evaluating residual capacity of an RC beam after exposure to different fire scenarios. Predictions from the numerical model are utilized to highlight importance of each stage of analysis in evaluating realistic residual capacity of fire damaged concrete members.